Development and performance evaluation of foxtail millet (Setaria italica L.) dehuller. (23rd November 2021) - Chikkaballapur Krishnappa, Sunil; Saravanan, Shanmugasundaram; Natarajan, Venkatachalapathy
Abstract: Foxtail millet dehuller for double stage dehulling was developed and evaluated. The machine consists of a hopper, two knurled rolls, two rubber rolls, an air blower, and a grader. The machine was evaluated for foxtail millet ( Setaria italica L.) at the different grain moisture content (10, 12, 14, and 17% [w.b.]), types of knurled rolls (diamond, angular, and straight knurled) and feed rate (100, 200, 300 kg/hr) for performance evaluation or efficiency. The maximum dehulling efficiency and cleaning efficiency of 82.24 and 82.47% was observed for 12% moisture content (w.b.), diamond‐type knurled roll and 100 kg/hr feed rate. Similarly, the maximum head grain yield of 97.82% and the minimum broken of 2.18% was observed for 12% moisture content (w.b.), diamond‐type knurled roll and 300 kg/hr feed rate. There was no significant change in the color values with the treatments. The predicted optimum condition for the machine is moisture content 12% (w.b.), diamond‐type knurled roll and feed rate of 100 kg/hr, which gave an optimum dehulling efficiency of 82.24%, head grain yield of 95.84%, broken of 4.16%, and cleaning efficiency of 82.47% with the desirability of 0.825. The economic analysis shows the suitability of the machine for small‐scale millet processors. Practical Applications: Dehulling of millets is an essential unit operation in millet processing. This study evaluated the performance analysis of the developed dehuller for foxtail millet at different grain moisture content, types of knurled rolls, and feed rate. The process parameters were optimized, which can be used to design the dehuller for millets. The results obtained show the relevance of applying the developed dehuller for foxtail millet applications, providing an alternative processing machine for millet processing.